Comparative Effects of 50% and 100% Pleurotus ostreatus Gel on TNF-α in Traumatic Ulcer Healing in Wistar Rats - Ni Nyoman Gemini Sari; Raziv Ganesha; Ni Nyoman Linda Pradnya Ningsih (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2026)
Introduction: White oyster mushroom (Pleurotus ostreatus) is a natural ingredient with diverse benefits, including its ability to heal traumatic ulcers. In the healing process, TNF-α acts as an inflammatory mediator that promotes epithelial growth and neovascularization. Material and Methods: This study was an in vivo laboratory experimental study using a post-test only control group approach, involving 32 samples randomly divided into eight treatment groups (n=4) based on variations in gel concentration (50%, 100%, negative control, and positive control) and observation time (days 3 and 7). TNF-α expression measurements were performed using an ELISA kit. Research data were analysed using the parametric One-Way ANOVA test, the non-parametric Kruskal-Wallis and Mann-Whitney tests, followed by the Tukey Post-Hoc test. Results and Discussions: Statistical analysis results showed a p-value of 0.000 <0.05 between treatment groups. Tumor Necrosis Factor-Alpha (TNF-α) expression decreased significantly in the groups given 50% and 100% white oyster mushroom extract gel, with the lowest average found at a concentration of 50% on both days 3 and 7, namely 231.33 and 195.33, thus demonstrating more optimal effectiveness at that concentration. Conclusion: White oyster mushroom (Pleurotus ostreatus) extract gel at a concentration of 50% was more effective than a concentration of 100% in reducing TNF-α expression in the healing of traumatic ulcers in male wistar rats. Further research with a concentration range of 50-100% and other immunological parameters is required for further confirmation.